PENYELESAIAN SENGKETA PEMBATALAN PENDAFTARAN MEREK (STUDI KASUS MEREK APOTEK GRAHA FARMA) - , Miladina Yustifika Amalia, SH; , Dr. Sulistiowati, S.H., M.Hum., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study examines and answers the problems about dispute settlement of registration cancellation of GRAHA FARMA drugstore mark, the criteria used by judges determining a well-known mark and legal entities name, and basic consideration of the judge to determine whether or not there are not elements of good faith in registration of mark on a judicial decision on the GRAHA FARMA drugstore mark. This research is a applied law research in two stages of the study namely: normative study is to conduct library research to collect and review of secondary data through document studies using library facilities and other media that allows to obtain and review the legal references related to the object of research, and empirical study is to conduct field research to obtain primary data by interview to the informant. In analyzing this research, the method which is used qualitative descriptive. In analyzing the qualitative data, this study used an Interactive Model of Analysis, ie the data gathered will be analyzed through three stages, namely reducing data, presenting data, and making conclusion. The results of this research show that, first the dispute settlement of registration cancellation of the mark is essentially the same as civil proceedings in general courts (District Court), the difference is the relatively short time and the judicial decision of the Commercial Court can not to appela, but the direct appeal to the Supreme Court. Second, the criteria used by judges determining the wellknown marks and legal entities name in the judicial decision on the GRAHA FARMA drugstore mark, according to the author it is less precise because of its reputation as a well known mark and legal entities name are not yet valid and they are still limited at the national level have not reached the international level. Third, the determination of whether or not there is a good faith element of registration of the mark on the judicial decision can not be separated from the underlying provisions of the Explanation of Article 4 of Act No. 15 of 2001.